(untitled) (Applied Biological Research, 2018)
Harvesting of summer crop of Baramasi lemon (Citrus limon) coincides with the rainy season that leads to low marketdemand and poor returns to the growers. Therefore, an experiment was planned for post-harvest degreening of lemon fruits to advance the marketing. Fully mature fruits of lemon cv. ‘PAU Baramasi Lemon-1’ were treated with different concentrations of ethephon solution viz., 0, 500, 750, 1000, 1250 and 1500 ppm for 5 min. Treated fruits were packed in CFB boxes with paper lining and kept at room temperature. Experimental fruits were analysed for physicochemical characteristics from 4th to 7th day after treatments at 24 h interval. Results revealed that maximum degreening of fruits occurred with ethephon @ 1500 ppm, which was depicted by ‘b*’ value (49.37, 50.83) of colour flex meter and these results were at par with ethephon @ 1250 ppm treatment. Similar trend was recorded for other parameters viz., physiological loss in weight, sensory quality, juice content, total soluble solids and acid content. It may be concluded that lemon fruits of cv. ‘PAU Baramasi Lemon-1’ harvested in June can be degreened in 6-7 days at room temperature by dipping in 1250 or 1500 ppm of ethephon so as to advance the marketing of summer crop.